Vivre avec ses peines : les fondements et les enjeux de l’usage de médicaments psychotropes saisis à travers l’expérience de femmes condamnées à l’emprisonnement à perpétuité - Hattem, Tina (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1991)
Taken from a qualitative empirical study on the experience of women condemned to life imprisonment, this article questions the use ofpsychotropic medication for purposes of self-control or the control of others. Concerned are the reasons contributing to the demand for and prescription of mood-altering drugs in prisons for women, the stakes involved in their use, and the need to take into account the conditions of detention as well as correctional and medical practices in the search for alternative solutions.